1993
DOI: 10.1155/s0962935193000754
|View full text |Cite
|
Sign up to set email alerts
|

LPS‐induced serum TNF production and lethality in mice: effect of L‐carnitine and some acyl‐derivatives

Abstract: The effect of L-carnitine and some of its acyl derivatives on serum TNF production and lethality in a murine experimental endotoxin shock model was investigated. In some instances, serum IL-6 production was also evaluated. In this experimental model, C57BL/6 mice received 30 mg/kg LPS (E. cell 055:B5) injected intraperitoneally, while L-carnitine and its derivatives were administered according to different schedules. Serum levels of TNF and IL-6 were evaluated 1 h following LPS injection. The treated animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
4
15
0
Order By: Relevance
“…Preliminary studies showed that intraperitoneal injection of 10 mg/kg of LPS induced significant amounts of TNF-a and IL-6 in mouse plasma with peak at 1 hour post-administration, which was consistent with that reported previously (Ruggiero et al, 1993;Gozzi et al, 1999). Pretreatment with AN3485 dosedependently decreased LPS-induced plasma levels of TNF-a and IL-6 in mice, with ED 50 and ED 90 values of approximately 8 and 30 mg/kg (Fig.…”
Section: Zymosansupporting
confidence: 91%
“…Preliminary studies showed that intraperitoneal injection of 10 mg/kg of LPS induced significant amounts of TNF-a and IL-6 in mouse plasma with peak at 1 hour post-administration, which was consistent with that reported previously (Ruggiero et al, 1993;Gozzi et al, 1999). Pretreatment with AN3485 dosedependently decreased LPS-induced plasma levels of TNF-a and IL-6 in mice, with ED 50 and ED 90 values of approximately 8 and 30 mg/kg (Fig.…”
Section: Zymosansupporting
confidence: 91%
“…The threshold dose of LPS required to induce this effect in the mouse was 300 µg. Some researchers have found that high doses of LPS induce a biphasic response in which an initial profound and prolonged decrease in temperature (Ruggiero et al, 1993) was followed by hyperthermia and fever (Wang et al, 1997), which may have been seen in this study had an intermediate dose of LPS e.g. 200 µg, been used.…”
Section: Discussionsupporting
confidence: 50%
“…The effect of LPS to decrease Tc has been reported before (Filkins and Luzio, 1968;Ruggiero et al, 1993;Wang et al, 1997;Wardlaw et al, 1971) and may be a dose-related phenomenon (Greer and Rietscjhel, 1978) which challenges the traditional view of LPS as a pyrogen (Cohen et al, 1986;Cooper, 1979;Freedman, 1960;Splawinski et al, 1977). The threshold dose of LPS required to induce this effect in the mouse was 300 µg.…”
Section: Discussionmentioning
confidence: 84%
“…Aureli et al [37] reported that ALCAR reduced both cholesterol and sphingomyelin in the brains of aged rats and proposed that the decrease in sphingomyelin was responsible for the decrease in cholesterol. Treatment with ALCAR has also shown to reverse age-associated increase in the levels of free and esterified cholesterol in plasma [38]. Glycolipids are glycosyl derivatives of lipids involved in a wide array of functions in the central nervous system including cell proliferation, differentiation, neurotransmission and apoptosis [39].…”
Section: Discussionmentioning
confidence: 99%